The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fimmu.2019.00661
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D/NKG2-Ligand Pathway Offers New Opportunities in Cancer Treatment

Abstract: The antitumor functions of NK cells are regulated by the integration of positive and negative signals triggered by numerous membrane receptors present on the NK cells themselves. Among the main activating receptors, NKG2D binds several stress-induced molecules on tumor targets. Engagement of NKG2D by its ligands (NKG2D-Ls) induces NK cell activation leading to production of cytokines and target cell lysis. These effects have therapeutic potential as NKG2D-Ls are widely expressed by solid tumors, whereas their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 121 publications
(117 reference statements)
0
55
0
1
Order By: Relevance
“…Therefore, the survival of CTCs might be a vulnerable aspect of malignant tumor metastasis, and thus the mechanism enabling CTCs to evade immune effector cell killing may be an important target for prospective cancer therapy research. Studies have shown that tumor cells may shed or otherwise restrict the presentation of NK‐cell receptor D (NKG2D) ligands, such as MICA, MICB, and ULBPs, involved in their recognition by NK cells or cytotoxic T lymphocytes (CTLs), or downregulate the expression of other factors that promote the activation of tumor‐specific immune responses . Furthermore, it is established that tumor cells that undergo EMT acquire phenotypic changes, involving the upregulation and downregulation of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the survival of CTCs might be a vulnerable aspect of malignant tumor metastasis, and thus the mechanism enabling CTCs to evade immune effector cell killing may be an important target for prospective cancer therapy research. Studies have shown that tumor cells may shed or otherwise restrict the presentation of NK‐cell receptor D (NKG2D) ligands, such as MICA, MICB, and ULBPs, involved in their recognition by NK cells or cytotoxic T lymphocytes (CTLs), or downregulate the expression of other factors that promote the activation of tumor‐specific immune responses . Furthermore, it is established that tumor cells that undergo EMT acquire phenotypic changes, involving the upregulation and downregulation of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It is a stress marker and is expressed in pathogenic bacteria, tumors, and organ transplant recipients [30]. MICA is the receptor of NKG2D, an important activating protein on the NK cell surface, and NK cells play a very important role in tumor innate immunity to kill tumor cells by recognizing tumor cell surface markers and producing a cytotoxic effect [51]. Previous studies have shown that high glucose protects pancreatic cancer from NK cell-mediated killing through suppressing MICA/B expression.…”
Section: Discussionmentioning
confidence: 99%
“…1E) (15,16). These molecules have been identified as targets for tumor immunosurveillance by the innate immune system and may elicit antitumor immunity without the requirement for conventional MHC-restricted antigen presentation (17). In addition, the two death receptors (i.e., TRAIL-R1 and TRAIL-R2) for TNFrelated apoptosis-inducing ligand (TRAIL) that induce cancer apoptosis as part of immune surveillance (18) were significantly upregulated in D3R3 (Fig.…”
Section: Decitabine Upregulates Surface Immune Molecules Related To γmentioning
confidence: 99%